Effect of the amount of reducing agent on surface structures, electrochemical activity and stability of PtRu catalysts - Lee, Kug-Seung; Yoo, Sung Jong; Jang, Jong Hyun; Sung, Yung-Eun (PERGAMON-ELSEVIER SCIENCE LTD, 2011)
The effect of the amount of reducing agent used in the synthesis of PtRu alloy catalysts on their surface structure was investigated, and the prepared catalysts were characterized using transmission electron microscopy, X-ray diffraction, X-ray photoelectron spectroscopy, cyclic voltammetry, and potential cycling. The alloying degree of the catalysts was essentially the same for all of the catalysts studied, despite the use of different amounts of reducing agent. Varying the amount of reducing agent resulted in changes in the surface composition of the catalysts, wherein the surfaces were found to be composed of several PtRu domains that differed in local inhomogeneity and hence showed differences in activity for COad oxidation. The highest activity for methanol oxidation was obtained when there was moderate Ru enrichment of the catalyst. The electrochemical stability of the catalysts was also investigated via potential cycling in a methanol-containing electrolyte solution. The electrochemical stability under methanol oxidation was enhanced by Ru-enrichment at the catalyst surface, because the Ru-rich surface had sufficient Ru atoms near the Pt atoms to act as a bifunctional catalyst, even though the Ru atoms were leached out by potential cycling. The most Ru-rich catalyst exhibited an increase in methanol oxidation current in the middle of potential cycling whereas the other catalysts showed a monotonic decrease. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: METHANOL FUEL-CELL; NANOPARTICLES; ELECTROCATALYSTS; ELECTROOXIDATION; ANODE; MODEL